An isomorphic subtype of long-term epilepsy-associated astrocytomas associated with benign prognosis - Blümcke, Ingmar; et al. (Acta Neuropathologica, 2004)
The semi-benign nature of diffuse astrocytomas is characterized by an increased risk for tumor recurrence and malignant transformation. In patients with intractable seizures, however, length of history and clinical follow-up studies indicate a better prognosis of this tumor entity. Here, we present a clinico-neuropathological study of 19 patients with chronic seizures and diffuse astrocytomas. In 6 patients, long-term survival and lack of tumor progression after a maximal follow-up time of 13 years appeared to correlate with a histologically isomorphic phenotype. Cytological hallmarks comprise low cellularity, lack of mitotic activity and highly differentiated astroglial elements infiltrating into adjacent brain parenchyma. Compared to " classical" variants of diffuse astrocytomas (WHO grade II), immunohistochemical reactions revealed a cellular proliferation below 1%, absence of nuclear p53 accumulation, and a lack of glial MAP2 and CD34 expression. Histopathologically, the isomorphic astrocytoma subtype can be distinguished from gangliogliomas, pilocytic astrocytomas and dysembryoplastic neuroepithelial tumors as well as from cortical dysplasia or reactive gliosis. Our data support the concept of a rare variant of diffuse astrocytomas occurring in young adults with long-term epilepsy and a favorable prognosis, which corresponds to WHO grade I. © Springer-Verlag 2004.
UnivIS-Import:2015-03-09:Pub.2004.med.nepa.npathw.anisom
Keywords: Brain; Glioma; Seizure; Tumor